Efektivitas Emulsi Ekstrak Rimpang Temulawak Sebagai Amara pada Mencit dengan Teknologi Potrtable - Surya Permana; Wildan Wildan; Santi Santi; Nelly Fitriani (Indonesian Journal of Pharmaceutical Education, 2023)
Temulawak rhizome (Curcuma xanthorrhiza Roxb.) is a plant that can increase appetite. The purpose of this study was to determine the concentration of the most effective emulsion working as amara in white male mice (Mus musculus). This study uses a sample extract Temulawak rhizomes (Curcuma xanthorrhiza Roxb.) at concentrations of 10%, 20%, and 30% were emulsified by testing the parameter requirements for evaluating emulsion preparations and their effectiveness as amara against white male mice (Mus musculus) by oral administration and positive control using Curvit syrup and aquadest as negative controls. The results of the physical evaluation of emulsion preparations included organoleptic tests, homogeneity tests, pH tests, viscosity tests and emulsion type tests. Tests for weight gain resulted in the difference between initial body weight and body weight after treatment for 21 days with an average of 1.6 grams at a concentration of 10%, a concentration of  20% of 2.2 grams, and a concentration of 30% of 4.2 grams. Based on statistical tests using one-way ANOVA and post-hoc tests, it can be concluded that the emulsion preparations extract temulawak rhizome (Curcuma xanthorrhiza Roxb.) has amara effectiveness at concentrations of 10%, 20%, and 30%, and at a concentration of 30% the greatest increase in body weight.